2014
DOI: 10.1007/s00277-014-2158-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human thrombopoietin promotes platelet engraftment after haploidentical hematopoietic stem cell transplantation: a prospective randomized controlled trial

Abstract: Delayed platelet engraftment (DPE) is a common complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT). This phenomenon is also a predictor of increased treatment-related mortality and poor survival. Therefore, therapies that promote platelet engraftment to prevent DPE are needed. This prospective randomized controlled trial was designed to investigate whether recombinant human thrombopoietin (rhTPO), administered subcutaneously at a daily dose of 15,000 U from the first day after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…However, when we stratified patients by disease type, we found that rhTPO significantly improved the OS of patients with MDS or AA. The results of our study are different from those reported by Han et al [24], in which rhTPO did not improve the prognosis of patients after allo-HSCT. The main reason for this difference may be that different patient populations were selected.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, when we stratified patients by disease type, we found that rhTPO significantly improved the OS of patients with MDS or AA. The results of our study are different from those reported by Han et al [24], in which rhTPO did not improve the prognosis of patients after allo-HSCT. The main reason for this difference may be that different patient populations were selected.…”
Section: Discussioncontrasting
confidence: 99%
“…The initial survival analysis of the entire cohort indicated that the use of rhTPO held no prognostic significance, as the OS of patients who received rhTPO was similar to that of patients who did not. These data are consistent with a report from Han et al, in which probabilities of OS and disease-free survival in patients after haploidentical HSCT did not differ between the rhTPO and non-rhTPO groups [24]. However, when we stratified patients by disease type, we found that rhTPO significantly improved the OS of patients with MDS or AA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations